Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Mercury and methylmercury in Hg-contaminated paddy soil and their uptake in rice as regulated by DOM from different agricultural sources - Ningla Yang; Jie Hu; Deliang Yin; Tianrong He; Xiang Tian; Shu Ran; Xian Zhou (Environmental Science and Pollution Research, 2023)

Effects of Composted Agricultural Organic Materials on Mercury Methylation in Paddy Soil and Mercury Enrichment in Rice - Zongfu Cheng; Tianrong He; Deliang Yin; Xiang Tian; Shu Ran; Xian Zhou (Bulletin of Environmental Contamination and Toxicology, 2023)

Remediation of Mercury-Polluted Farmland Soils: A Review - Deliang Yin; Xian Zhou; Tianrong He; Pan Wu; Shu Ran (Bulletin of Environmental Contamination and Toxicology, 2022)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Mercury Bioaccumulation in Freshwater Snails as Influenced by Soil Composition - Ge Zhang; Deliang Yin; Tianrong He; Yiyuan Xu; Shu Ran; Xian Zhou; Xiang Tian; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Chemical composition and antioxidant activity of the essential oil of endemic Viola tianshanica - Jin Yang; Zhen Qu; Yu-Ling Xiao; Guo-Fu Qiu; Tao Zhang; Zhong-Yuan Wu; Xian-Ran He; Xian-Ming Hu (Natural Product Research, 2011)